Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the values of the constants \( p \), \( q \), and \( r \) in the function \( f(x) = p x^2 + q x + r \) given the conditions \( f(0) = 4 \), \( f(-1) = 6 \), and \( f(-2) = 18 \), we follow these steps:
1. Substitute \( x = 0 \) into the function:
[tex]\[ f(0) = p(0)^2 + q(0) + r = r \][/tex]
We know \( f(0) = 4 \), so:
[tex]\[ r = 4 \][/tex]
2. Substitute \( x = -1 \) into the function:
[tex]\[ f(-1) = p(-1)^2 + q(-1) + r = p(1) - q + r = p - q + r \][/tex]
We know \( f(-1) = 6 \), so:
[tex]\[ p - q + r = 6 \][/tex]
Substituting \( r = 4 \) from the first condition:
[tex]\[ p - q + 4 = 6 \implies p - q = 2 \quad \text{(Equation 1)} \][/tex]
3. Substitute \( x = -2 \) into the function:
[tex]\[ f(-2) = p(-2)^2 + q(-2) + r = p(4) - 2q + r = 4p - 2q + r \][/tex]
We know \( f(-2) = 18 \), so:
[tex]\[ 4p - 2q + r = 18 \][/tex]
Substituting \( r = 4 \) from the first condition:
[tex]\[ 4p - 2q + 4 = 18 \implies 4p - 2q = 14 \quad \text{(Equation 2)} \][/tex]
4. Solve the system of equations derived from steps 2 and 3:
From Equation 1:
[tex]\[ p - q = 2 \][/tex]
From Equation 2:
[tex]\[ 4p - 2q = 14 \][/tex]
We can solve these equations simultaneously. First, solve Equation 1 for \( p \):
[tex]\[ p = q + 2 \][/tex]
Substitute \( p = q + 2 \) into Equation 2:
[tex]\[ 4(q + 2) - 2q = 14 \][/tex]
Simplify and solve for \( q \):
[tex]\[ 4q + 8 - 2q = 14 \implies 2q + 8 = 14 \implies 2q = 6 \implies q = 3 \][/tex]
5. Find \( p \) using the value of \( q \):
[tex]\[ p = q + 2 = 3 + 2 = 5 \][/tex]
Hence, the values of the constants are:
[tex]\[ p = 5, \quad q = 3, \quad r = 4 \][/tex]
1. Substitute \( x = 0 \) into the function:
[tex]\[ f(0) = p(0)^2 + q(0) + r = r \][/tex]
We know \( f(0) = 4 \), so:
[tex]\[ r = 4 \][/tex]
2. Substitute \( x = -1 \) into the function:
[tex]\[ f(-1) = p(-1)^2 + q(-1) + r = p(1) - q + r = p - q + r \][/tex]
We know \( f(-1) = 6 \), so:
[tex]\[ p - q + r = 6 \][/tex]
Substituting \( r = 4 \) from the first condition:
[tex]\[ p - q + 4 = 6 \implies p - q = 2 \quad \text{(Equation 1)} \][/tex]
3. Substitute \( x = -2 \) into the function:
[tex]\[ f(-2) = p(-2)^2 + q(-2) + r = p(4) - 2q + r = 4p - 2q + r \][/tex]
We know \( f(-2) = 18 \), so:
[tex]\[ 4p - 2q + r = 18 \][/tex]
Substituting \( r = 4 \) from the first condition:
[tex]\[ 4p - 2q + 4 = 18 \implies 4p - 2q = 14 \quad \text{(Equation 2)} \][/tex]
4. Solve the system of equations derived from steps 2 and 3:
From Equation 1:
[tex]\[ p - q = 2 \][/tex]
From Equation 2:
[tex]\[ 4p - 2q = 14 \][/tex]
We can solve these equations simultaneously. First, solve Equation 1 for \( p \):
[tex]\[ p = q + 2 \][/tex]
Substitute \( p = q + 2 \) into Equation 2:
[tex]\[ 4(q + 2) - 2q = 14 \][/tex]
Simplify and solve for \( q \):
[tex]\[ 4q + 8 - 2q = 14 \implies 2q + 8 = 14 \implies 2q = 6 \implies q = 3 \][/tex]
5. Find \( p \) using the value of \( q \):
[tex]\[ p = q + 2 = 3 + 2 = 5 \][/tex]
Hence, the values of the constants are:
[tex]\[ p = 5, \quad q = 3, \quad r = 4 \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.